Penerapan Web Content Accessibility Guidelines dan Design Thinking dalam Perancangan UI/UX Aplikasi Ujian Online - Silvana Rasio Henim; Erzi Hidayat; Maksum Ro'is Adin Saf (Sekawan Institut, 2026)
The most significant change in education due to the pandemic is the implementation of online evaluation methods. Online exams provide students with the flexibility to take tests from any lo-cation. Although online examinations offer flexibility for learners to participate from any loca-tion, their implementation still faces various challenges, such as the potential for cheating, tech-nical disruptions, and limited accessibility for users with diverse physical conditions and digital competencies. These issues highlight the need for designing online examination interfaces that are not only easy to use but also inclusive. This study aims to design the user interface and user expe-rience by employing the design thinking approach and applying the Web Content Accessibility Guidelines (WCAG) to enhance interface accessibility starting from the design phase. The WCAG 2.0 standard, developed by the W3C, is applied as a guideline for meeting accessibility require-ments. The WCAG principles implemented include perceivability, operability, understandability, and robustness. Usability testing on the prototype was conducted using the System Usability Scale (SUS), scoring 69. This score indicates that the designed prototype falls into the